2009
DOI: 10.1093/ndt/gfp078
|View full text |Cite
|
Sign up to set email alerts
|

R-568 reduces ectopic calcification in a rat model of chronic kidney disease-mineral bone disorder (CKD-MBD)

Abstract: Thus, R-568, with or without Ca, improved the biochemical abnormalities of hyperparathyroidism but with higher and lower calcium levels, respectively, compared with controls. However, R-568 + Ca had more dramatic improvement in bone volume, but more extraskeletal calcification than R-568 alone. This complexity demonstrates that treatment of one component of CKD-MBD may lead to undesirable effects on other components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 24 publications
1
43
2
Order By: Relevance
“…AMG 416 (Velcalcetide) Activates the Calcium Sensing Receptor previously demonstrated that calcimimetics (such cinacalcet or homologs thereof) can delay or slow calcification in uremic rats (Lopez et al, 2006;Moe et al, 2009). In line with these observations, treatment of uremic rats with AMG 416 decreased renal mineralization compared with vehicle-treated uremic rats.…”
Section: Downloaded Frommentioning
confidence: 81%
“…AMG 416 (Velcalcetide) Activates the Calcium Sensing Receptor previously demonstrated that calcimimetics (such cinacalcet or homologs thereof) can delay or slow calcification in uremic rats (Lopez et al, 2006;Moe et al, 2009). In line with these observations, treatment of uremic rats with AMG 416 decreased renal mineralization compared with vehicle-treated uremic rats.…”
Section: Downloaded Frommentioning
confidence: 81%
“…In rodent models, treatment with a calcimimetic lowered heart calcium content compared with control animals, whereas calcimimetic plus calcium did not. 28 Other studies showed that calcimimetics reduced arterial calcification compared with calcitriol and paricalcitol. 29,30 In a randomized trial of patients receiving hemodialysis, treatment with cinacalcet and lowdose vitamin D compared with flexible doses of vitamin D alone slowed the progression of coronary artery calcification on electron-beam computed tomography, with nominally significant changes as assessed with the volumetric method of The reduction of FGF23 with cinacalcet occurred within the first 20 weeks and was maintained throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…16 The animals utilized for the present study represent a subset of animals in a separate publication in which the effect of R-568 on extraskeletal calcification and bone were examined. 17 We performed immunohistochemistry on paraffin sections of kidney using a primary antibody to the CaR and a secondary antibody with a peroxidase chromagen product. We deparaffinized tissue sections (kidney and human parathyroid) in xylene and rehydrated them in descending alcohol concentrations.…”
Section: Concise Methodsmentioning
confidence: 99%